2018
DOI: 10.1186/s12898-018-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the distribution of Stipa purpurea across the Tibetan Plateau via the MaxEnt model

Abstract: BackgroundThe ecosystems across Tibetan Plateau are changing rapidly under the influence of climate warming, which has caused substantial changes in spatial and temporal environmental patterns. Stipa purpurea, as a dominant herbsage resource in alpine steppe, has a great influence on animal husbandry in the Tibetan Plateau. Global warming has been forecasted to continue in the future (2050s, 2070s), questioning the future distribution of S. purpurea and its response to climate change. The maximum entropy (MaxE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 49 publications
4
90
0
1
Order By: Relevance
“…For those models that needed presence/absence data, we generated 1,000 random absence records outside the distribution area (ED) (Tognelli, Roig‐junent, Marvaldi, Flores, & Lobo, ), where the evidence in the last 100 years showed that B. alternatus does not presently occur but rather became true absences, which are based on reliable field evidence of nonoccurrence (Figure c) (Saupe et al., ). Moreover, several studies obtained good performance using pseudo‐absence/absence data outside a predefined region based on a minimum distance to the presence (Barbet‐Massin et al., ; Lobo, Jiménez‐Valverde, & Hortal, ). This way of generated absence records is recommended when using classification and machine‐learning techniques (Barbet‐Massin et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For those models that needed presence/absence data, we generated 1,000 random absence records outside the distribution area (ED) (Tognelli, Roig‐junent, Marvaldi, Flores, & Lobo, ), where the evidence in the last 100 years showed that B. alternatus does not presently occur but rather became true absences, which are based on reliable field evidence of nonoccurrence (Figure c) (Saupe et al., ). Moreover, several studies obtained good performance using pseudo‐absence/absence data outside a predefined region based on a minimum distance to the presence (Barbet‐Massin et al., ; Lobo, Jiménez‐Valverde, & Hortal, ). This way of generated absence records is recommended when using classification and machine‐learning techniques (Barbet‐Massin et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained the ROC curve, that is, AUC index, which represents the probability that the model correctly predicted the observed presences and absences and varies from 0 to 1, 1 being perfect discrimination and 0.5 to 0 implying a discrimination worse than random Elith et al, 2006). One of the greatest advantages of the ROC curve (AUC) is that it is threshold independent (Lobo, Jiménez-Valverde, & Real, 2008); however, its use and efficiency has been widely criticized (Jiménez-Valverde, 2012;Lobo et al, 2008), although it continues to be used in the literature (e.g., Ma & Sun, 2018;Taylor, Papeş, & Long, 2018). Other metrics have been proposed to evaluate SDMs (see Hijmans, 2012;Phillips & Elith, 2010), despite this, no measure has succeeded in replacing AUC, which is still being used in more than 80% of SDMs studies (Fourcade et al, 2018).…”
Section: Validation and Evaluation Methodsmentioning
confidence: 99%
“…MaxEnt model is considered one of the most efficient tools to predict species distribution with presence-only data, leading to its widespread use (Aryal eT al., 2016;Gomes et al, 2018;Lamsal, Kumar, Aryal, & Atreya, 2018;Ma & Sun, 2018;Phillips, Anderson, & Schapire, 2006). The parameters of MaxEnt model were set to: 25% for random test percentage and 1 regularization multiplier.…”
Section: Habitat Suitability Modelmentioning
confidence: 99%
“…Suitability indices describe the relationship between habitat suitability score and a given environmental variable of a target species. Habitat suitability is a way to predict the suitability of habitat at a certain location for a given species or group of species based on their observed affinity for particular environmental conditions (Yi et al, 2016;Ma, Sun, 2018). SDMs therefore have been widely used for predicting distributions of species in terrestrial, freshwater and marine environments, and across taxa from many biological groups (Elith, Leathwick, 2009), with increasing numbers of publications each year (Robinson et al, 2011;Brotons, 2014).…”
Section: Introductionmentioning
confidence: 99%